Development of effective and sustainable adsorbent biomaterial from an agricultural waste material: Cu(II) removal - Asim N.; Amin M.H.; Samsudin N.A.; Badiei M.; Razali H.; Akhtaruzzaman M.; Amin N.; Sopian K. (Elsevier Ltd, 2023)
Adsorbents; Agricultural robots; Agricultural wastes; Agriculture; Biomaterials; Chemicals removal (water treatment); Design of experiments; Driers (materials); Efficiency; Heavy metals; Moisture; Waste treatment; Water absorption; Adsorbent materials; Adsorption properties; Alkali concentrations; Heavy metal removal; Moisture absorption property; Optimized conditions; Removal efficiencies; Value added products; Copper compounds